PRODUCTION OF MILK IN STERILE OR VIRGIN COWS WITH USE OF DIETHYLETHYLBESTROL DIPROPIONATE - MOLERES RUIZ, RODOLFO (Hospital General, CD MEXICO, DF, MEX, 1976)
The van Slyke method was used to determine the distribution of amino acids in the proteins of the corixid (hemipterous insects) eggs frequently used as food in Mexico Of the total N, arginine comprised 143%, cystine 09%, histidine 75%, lysine 58%, pr
CLIN GENET
Keywords: PRODUCTION OF MILK, STERILE OR VIRGIN COWS, DIETHYL ETHYLBESTROL DIPROPIONATE; MULTIDISCIPLINARIA; PRODUCCION ANIMAL; SISTEMAS DE PRODUCCION GANADERA